Implementasi Karakter Religius dalam Pembelajaran Sains Laboratorium Medik di Pondok Pesantren Queen Al Ishlah Banyuwangi - Qomariyah, Ani; Abror, Nailul (Proceedings of Annual Conference on Community Engagement, 2022)
In the midst of moral decadence that is increasingly acutely attacking the human heart, character education has become a hot topic of conversation in various countries. The facts on the ground show that the implementation of character education is not as easy as turning the palm of the hand. Based on the results of observations at the Queen Al Ishlah Islamic Boarding School Banyuwangi that in learning science, especially in Health Biology material (Medical Laboratory Science), they still tend to use the lecture method. Therefore, the lecturer of the Medical Laboratory Technology D-IV Study Program seeks to introduce project learning methods to the material of Medical Laboratory Science based on strengthening religious character education for students. The method used in this community service activity consists of three stages: preparation, implementation, and evaluation. This service activity yielded several results. The religious character of the students in Medical Laboratory Science learning through the project method showed an average score of 79.90% with Good criteria. The religious character of gratitude gets the highest score compared to other religious characters, which is 83.00%. The students who have high self-efficacy (average score of 81.25%) produce better religious character than the students who have low efficacy (average score of 68.75%). Based on the summary results of the Kruskal-Wallis test, there is an effect between project method-based Medical Laboratory Science learning and religious character education for students.